64.8k views
1 vote
HELP THIS IS DUE TODAY
(-9-√-32)-(2+√-8)

User Toothful
by
6.5k points

2 Answers

1 vote

Answer:


-11-6√(2)\:i

Explanation:

Given expression:


\left(-9-√(-32)\right)-\left(2+√(-8)\right)

Remove the parentheses:


\implies -9-√(-32)-2-√(-8)

Rewrite -32 as 16 · 2 · -1 and rewrite -8 as 4 · 2 · -1 :


\implies -9-√(16 \cdot 2\cdot -1)-2-√(4 \cdot 2\cdot -1)


\textsf{Apply radical rule} \quad √(ab)=√(a)√(b):


\implies -9-√(16) √(2) √(-1)-2-√(4)√(2)√(-1)

Simplify and apply the imaginary number rule √(-1) = i


\implies -9-4√(2)\:i -2-2√(2)\:i

Group like terms:


\implies -9-2-4√(2)\:i -2√(2)\:i

Combine like terms:


\implies -11-6√(2)\:i

User Alexander Art
by
5.6k points
1 vote

Answer:


  • -11-6i√(2)

----------------------------------------------------

Simplify the expression:


  • (-9-√(-32) )-(2+√(-8) )=

  • (-9-√(-1*2*16) )-(2+√(-1*2*4) )=

  • (-9-4i√(2) )-(2+2i√(2) )=

  • -9-4i√(2) -2-2i√(2) =

  • -11-6i√(2)
User Borek Bernard
by
6.3k points